Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure, I'd be happy to help you solve the equation [tex]\(-2(x-4)^2 + 3 = -69\)[/tex] step-by-step.
### Step-by-Step Solution
1. Start with the given equation:
[tex]\[ -2(x - 4)^2 + 3 = -69 \][/tex]
2. Subtract 3 from both sides to isolate the quadratic term:
[tex]\[ -2(x - 4)^2 + 3 - 3 = -69 - 3 \][/tex]
Simplifying, we get:
[tex]\[ -2(x - 4)^2 = -72 \][/tex]
3. Divide both sides by -2 to make the coefficient of [tex]\((x - 4)^2\)[/tex] equal to 1:
[tex]\[ \frac{-2(x - 4)^2}{-2} = \frac{-72}{-2} \][/tex]
Simplifying, we get:
[tex]\[ (x - 4)^2 = 36 \][/tex]
4. Take the square root of both sides to solve for [tex]\(x - 4\)[/tex]:
[tex]\[ x - 4 = \pm\sqrt{36} \][/tex]
Since [tex]\(\sqrt{36} = 6\)[/tex], we have two possible solutions:
[tex]\[ x - 4 = 6 \quad \text{or} \quad x - 4 = -6 \][/tex]
5. Solve each equation for [tex]\(x\)[/tex]:
- For [tex]\(x - 4 = 6\)[/tex]:
[tex]\[ x - 4 = 6 \quad \Rightarrow \quad x = 6 + 4 \quad \Rightarrow \quad x = 10 \][/tex]
- For [tex]\(x - 4 = -6\)[/tex]:
[tex]\[ x - 4 = -6 \quad \Rightarrow \quad x = -6 + 4 \quad \Rightarrow \quad x = -2 \][/tex]
### Final Solutions
Thus, the solutions to the equation [tex]\(-2(x-4)^2 + 3 = -69\)[/tex] are:
[tex]\[ x = 10 \quad \text{and} \quad x = -2 \][/tex]
### Step-by-Step Solution
1. Start with the given equation:
[tex]\[ -2(x - 4)^2 + 3 = -69 \][/tex]
2. Subtract 3 from both sides to isolate the quadratic term:
[tex]\[ -2(x - 4)^2 + 3 - 3 = -69 - 3 \][/tex]
Simplifying, we get:
[tex]\[ -2(x - 4)^2 = -72 \][/tex]
3. Divide both sides by -2 to make the coefficient of [tex]\((x - 4)^2\)[/tex] equal to 1:
[tex]\[ \frac{-2(x - 4)^2}{-2} = \frac{-72}{-2} \][/tex]
Simplifying, we get:
[tex]\[ (x - 4)^2 = 36 \][/tex]
4. Take the square root of both sides to solve for [tex]\(x - 4\)[/tex]:
[tex]\[ x - 4 = \pm\sqrt{36} \][/tex]
Since [tex]\(\sqrt{36} = 6\)[/tex], we have two possible solutions:
[tex]\[ x - 4 = 6 \quad \text{or} \quad x - 4 = -6 \][/tex]
5. Solve each equation for [tex]\(x\)[/tex]:
- For [tex]\(x - 4 = 6\)[/tex]:
[tex]\[ x - 4 = 6 \quad \Rightarrow \quad x = 6 + 4 \quad \Rightarrow \quad x = 10 \][/tex]
- For [tex]\(x - 4 = -6\)[/tex]:
[tex]\[ x - 4 = -6 \quad \Rightarrow \quad x = -6 + 4 \quad \Rightarrow \quad x = -2 \][/tex]
### Final Solutions
Thus, the solutions to the equation [tex]\(-2(x-4)^2 + 3 = -69\)[/tex] are:
[tex]\[ x = 10 \quad \text{and} \quad x = -2 \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.